2020
DOI: 10.1021/acs.biochem.0c00576
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of Extracellular Histidine Residues of GPR68 for Proton-Sensing and Allosteric Modulation by Divalent Metal Ions

Abstract: GPR68, an orphan G-protein coupled receptor, senses protons, couples to multiple G-proteins, and is also activated or inhibited by divalent metal ions. It has seven extracellular histidine residues, although it is not clear how these histidine residues play a role in both proton-sensing and metal ion modulation. Here we demonstrate that divalent metal ions are allosteric modulators that can activate or inhibit proton activity in a concentration-and pH-dependent manner. We then show that single histidine mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 76 publications
5
23
0
Order By: Relevance
“…Moreover, conditions that stimulate each receptor, i.e., reduction of extracellular pH for OGR1 and elevation of extracellular calcium for CaSR, inhibit the signaling dependent on the other receptor. Interestingly, another study performed by Huang et al with HEK293T cells showed that extracellular calcium had a small stimulatory effect on OGR1 [38]. The discrepancy might be explained by endogenous CaSR expression in HEK293T [33,133].…”
Section: Interactions Among Proton-activated Receptors and With Other...mentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, conditions that stimulate each receptor, i.e., reduction of extracellular pH for OGR1 and elevation of extracellular calcium for CaSR, inhibit the signaling dependent on the other receptor. Interestingly, another study performed by Huang et al with HEK293T cells showed that extracellular calcium had a small stimulatory effect on OGR1 [38]. The discrepancy might be explained by endogenous CaSR expression in HEK293T [33,133].…”
Section: Interactions Among Proton-activated Receptors and With Other...mentioning
confidence: 95%
“…Only a few amino acids are protonated at pH values ranging from 5 to 7.4, such as histidine, aspartic acid, arginine, lysine, and glutamic acid [107]. Research on proton sensing by GPCRs has mostly focused on the role of histidine residues [38,75,100,107]. Several histidine residues are present in the extracellular loops of TDAG8, GPR4, and OGR1, but only few in G2A, which could explain the low pH sensitivity of this receptor [100].…”
Section: Proton-activated Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“… 108 Interestingly, another study in HEK293T cells shows that divalent metal ions can enhance GPR68 signaling. 109 In organotypic hippocampal and cortical slices, we found that acidosis induced the activation of PKC, and this effect requires GPR68. 63 These results suggest that, in both organotypic brain slices and cerebellar granule cells, GPR68 activation by acidosis activates the Gq-DAG-PKC axis.…”
Section: The Proton-sensitive Receptorsmentioning
confidence: 83%
“…A family of proton-sensing G-protein-coupled receptors (GPCRs), ovarian cancer G-protein-coupled receptor 1 (OGR1, also known as GPR68), G-protein-coupled receptor 4 (GPR4), and T-cell death-associated gene 8 (TDAG8, also known as GPR65), is activated by protons by differing degrees of sensitivity to pH [14]. Protons bind to histidine residues located at the extracellular region of these transmembrane receptors, activating second messenger signalling pathways, which in turn regulate gene expression [14][15][16][17]. OGR1 is almost silent or inactive at pH 7.8, but fully active at pH ≤ 6.8 [14].…”
Section: Introductionmentioning
confidence: 99%